Screening of Culture Conditions for Production of Xylanase from Landfill Soil Bacteria - Siti Nor Amira Rosli; Rohaida Che Man; Nasratun Masngut (Indonesian Journal of Chemistry, 2019)
Culture conditions including initial pH media, incubation period, inoculum size, type of carbon source, type of nitrogen source and its concentration, which affect xylanase production were screened via the one-factor-at-a-time approach. The bacteria used in the production of xylanase was isolated from the landfill site at Sg. Ikan, Kuala Terengganu, Malaysia. Three characterizations of the landfill soil were investigated for their moisture content, ash content, and pH. The culture conditions range used in the experimental work were between 6–30 h for the incubation period, with initial pH between 5–9, inoculum size between 1–20% v/v, carbon, nitrogen sources, and nitrogen source concentration between 1–5% w/v. Xylanase activity was estimated using dinitrosalicylic acid (DNS) based on the release of xylose under standard assay conditions. The landfill soil was observed to have pH between pH 3.4–7.2 with a moisture content between 12.4–33.7% and ash ranged between 3.5–4.3%. Results showed that the highest xylanase activity within studied ranges was recorded at 25.91±0.0641 U/mL with 10% (v/v) inoculum size, 1% (w/v) xylose as sole carbon source, mixture of 1% (w/v) peptone and 0.25% (w/v) ammonium sulphate as nitrogen sources, which was carried out at initial pH of 8.0 for 24 h incubation.